Protective effect of early serum from mice after cytomegalovirus infection. - Araullo-Cruz, T P (1978)
Serum obtained from mice 3 to 5 days after cytomegalovirus infection contained complement-requiring neutralizing antibody, which, when passively transferred, protected mice from lethal infection with the homologous virus. The active substance was largely heat-stable 7s immunoglobulin.